Consumer preferences and electricity pricing reform in Western Australia - Tayal, Dev; Evers, U. (Elsevier, 2018)
© 2018 Elsevier Ltd Australia's electricity prices are high, driven by rising peak demand that is forcing significant levels of infrastructure investment. Compounding these factors is the lack of transparent price signals for consumers, with uniform pricing structures providing no incentive to change consumption behaviours. This research surveyed residential electricity consumers in Western Australia about their perceptions of solar, consumption behaviour, and electricity pricing structures. The results suggest that customers in Western Australia may be willing to change behaviour, reduce electricity usage, and be rewarded for use of renewable technologies, highlighting an opportunity for policies such as retail tariff reform to be further explored.